GEOGRAFI VARIASI BAHASA DI BAGIAN UTARA KARAWANG JAWA BARAT - Huri, Daman; Daman Huri (Universitas PGRI Sumatera Barat, 2017)
This research is motivated by the findings that Karawang has several languages because it is caused by the number of urban, this is triggered by the change of Karawang regency into industrial area. Karawang northern part of the district that has a variation of colored languages because it has a history of language transition. Qualitative descriptive method and dialiektologi method is the method used in this study. The purpose of this study is to obtain the language variations contained in the northern part of Karawang. From the results of research found four languages namely Sundanese, Cirebon, Betawi Malay, and Bekasi Malay language spread with varied in eight districts, in the northern part of Karawang. Keyword: Geography, language variation